High spatial variations of potential nitrification and N2O production across the Yangtze River and associated major tributaries - Caixia Lan; Qiuxun Lin; Mengting Qi; Yuxuan Fu; Guosen Zhang; Ye Li; Min Liu; Lijun Hou; Xiaofei Li (Water Research, 2026)

Coupling iron amendment with Celosia argentea for the concurrent stabilization of arsenic and phytoextraction of cadmium in co-contaminated soils - Mengting Lin; Xusheng Jiang; Xuehong Zhang; Wei Zhao; He Gong; Jie Liu (Journal of Environmental Chemical Engineering, 2026)

The membrane receptor Basigin facilitates WSSV infection by binding envelope proteins and suppressing antiviral gene expression in shrimp - Wanli Lu; Tongxin Lin; Mengting Luo; Yuxin Shi; Zhaohua Chen; Siyou Huang; Linwei Yang (Fish & Shellfish Immunology, 2026)

Decline of beneficial microbes and proliferation of latent pathogens: Key drivers of postharvest disease in citrus - Jianghua Chen; Mengting Xu; Ting Zhu; Ziyi Yang; Juan Liu; Jie Duan; Yang Lin; Xiao Yu; Daohong Jiang; Yanping Fu (Postharvest Biology and Technology, 2026)

In vitro regeneration of Lily bulblets and artificial seeds development - Zhengjing Wu; Yuan Long; Luping Cui; Mengting Ma; Xun Liu; Zijing Lin; XinYi Wu; Yifang Su (Journal of Plant Biochemistry and Biotechnology, 2026)

Antibiotic sensitivity as a key Determinant: B. Subtilis Reshapes the Microecology to mitigate antibiotic resistance genes during composting - Xiaoxia Hao; Lijia Jiang; Mengting Chen; Shuo Liu; Li Zhu; Dongmei Jiang; Lin Bai (Bioresource Technology, 2026)

Contrasting roles of precipitation and dust in regulating organic–inorganic carbon burial in Tibetan lakes across aridity gradients - Mengting Zhao; Yongquan Lin; Lingmei Xu; Zhitong Chen; Wengang Kang; Xinwei Yan; Jianbao Liu (Journal of Geographical Sciences, 2026)

Spatial and historic changes of nutrients across the changjiang river and associated major tributaries - Qiuxun Lin; Zhenyang Song; Mengting Qi; Guoyu Yin; Dongyao Sun; Ye Li; Lijun Hou; Min Liu; Xiaofei Li (Water Research, 2026)

SEMA3E promotes beige adipocyte differentiation and thermogenesis via β-catenin signaling in mice - Chenxi Xiao; Zhenghua Su; Jialin Zhao; Yajie Hu; Mengting He; Shenhan Xu; Ruoxue Chen; Jie Xu; Jun Chang; Chengshou Lin; Xinhua Liu; Wugui Chen (Apoptosis, 2026)

Enantioselective study of hexythiazox in earthworms (Eisenia fetida): Bioaccumulation, degradation, enantiomer-specific profiling and perturbed metabolic pathways - Mengting Zhang; Yiyun Cai; Qixing Tang; Cancan Yang; Xiaojiang Ke; Jirui Wang; Lin He; Ping Zhang (Pesticide Biochemistry and Physiology, 2025)

A new insight of size-dependent plastics particles kinetics with regarding of metabolomics effects in liver and kidney - Hongying Gao; Jing Li; Zehua Xu; Yiyang Duan; Bowen Su; Mengting Li; Banyun Zheng; Miaomiao Ren; Hao Chang; Heng Wang; Yi Lin; Heqing Shen (Environmental Pollution, 2025)

Temperature shapes the global distribution of organic carbon in lake surface sediments - Yongquan Lin; Sheng Yang; Mengting Zhao; Xuerui Lyu; Lingmei Xu; Wengang Kang; Xinwei Yan; Yurui Zhang; Jianbao Liu (Journal of Geographical Sciences, 2025)

Improving terrestrial solar-induced chlorophyll fluorescence (SIF) reconstruction through multi-satellite-derived SIF integration: a comparative study in regional scale - Mengting Pan; Xiaofeng Lin; Zhongyong Xiao; Fei Wang; Lifeng Guo; Cuiping Wang; Jinghan Xie; Jingchun Fang (International Journal of Remote Sensing, 2025)

Machine learning and soil spectra enable rapid identification of multiple heavy metals at the continental scale - Chongchong Qi; Tao Hu; Mengting Wu; Ping Zhang; Sybil Derrible; Di Wang; Yong Sik Ok; Zhang Lin (Journal of Environmental Chemical Engineering, 2025)

Optimizing KH2PO4 addition to enhance nitrogen retention in swine manure composting: Integrated mechanisms of enzyme activity, microbial community, and denitrification genes - Xiaoxia Hao; Lijia Jiang; Du Jin; Mengting Chen; Wenyi Wang; Dongmei Jiang; Lin Bai (Journal of Environmental Chemical Engineering, 2025)

Stepwise recovery of gallium (Ga), lithium (Li), and rare earth elements (REEs) from roasted coal gangue based on leaching kinetics differentiation - Jingzheng Wang; Hongxiang Xu; Yijun Cao; Kejia Ning; Biao Fu; Lin Ma; Xin Sun; Yuntao Kang; Mengting Hong; Guixia Fan; Xiahui Gui; Jiushuai Deng (Hydrometallurgy, 2025)

Spatiotemporal dynamics and drivers of multidimensional carbon emission eco-efficiency: A case study of Guangdong Province, China - Yihan Wang; Mengting Lin; Hui Zeng (Journal of Environmental Management, 2025)

In-situ construction of BiOBr/UiO-66(Zr/Ce) S-scheme heterojunction for efficient selective photocatalytic CO2 reduction to CO - Mengting Shen; Ling Wang; Man Zhou; Liwei Lin; Han Li; Yanan Wang; Song Xu; Zhongyu Li (Fuel, 2025)

Systemic assessment of fenpropathrin and 3-phenoxybenzoic acid in soil: adsorption, desorption, and effects on soil enzyme and microbial community - Ping Zhang; Xiaojiang Ke; Mengting Zhang; Cancan Yang; Yiyun Cai; Lin He (Pesticide Biochemistry and Physiology, 2025)

Versatile fabrication of hydrogel coatings with shell powder as a key Ingredient - Feng Li; Jianwan Lin; Yongqi Li; Shijia Wu; Cha Wen; Mengting Mo; Linfeng Huang; Ning Qing; Zhenpin Lu; Xing Jiang; Liuyan Tang (Chemical Engineering Journal, 2025)

Determination of the spatiotemporal evolution patterns and obstacle factors of coupling coordination of the water–energy–food–ecology system in Ordos City, China - Jihong Qu; Jixian Lin; Mengting Cheng; Zezhong Zhang; Kai Feng; Fei Wang; Kun Ren; Juan Zhou; Yanbin Li (Environmental Geochemistry and Health, 2025)

Ecological disposal of bauxite tailings and red mud: A sustainable strategy for bauxite industrial waste reuse - Xusheng Jiang; Xuehong Zhang; Xijun Liu; Hui Qiu; Mengting Lin; Guo Yu; Shouhui Zhang; Jie Liu (Resources, Conservation and Recycling, 2025)

Nanomorphic copper phosphate as a lightless catalyst for singlet oxygen generation: Mechanistic insights and comparative analysis - Weihao Cong; Lin Zang; Mengting Pan; Liyuan Zhang; Yan Zhao; Weiheng Kong (Journal of Environmental Chemical Engineering, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

In vitro releasing characteristics of bound phenolics from mangosteen (Garcinia mangostana L.) pericarp dietary fiber and its role in gut microbiota regulation - Xiaozhen Liu; Runyu Liao; Mengting Lai; Fuxiang Li; Lichao Zhao; Yuting Li; Fengyuan Liu; Jingkun Yan; Lin Li (Food Bioscience, 2025)

Superhydrophobic, conductive and magnetic sponge for high performance oil-water separation and recycled oil absorption - Yuzhe Zhang; Changqing Wu; Siyu Wu; Minghao Pan; Mengting Shen; Wang Zhang; Ziyao Zhou; Zhongyu Li; Liwei Lin (Journal of Environmental Chemical Engineering, 2024)

Wogonin induces mitochondrial apoptosis and synergizes with venetoclax in diffuse large B-cell lymphoma - Ye Lin; Xia Jiang; Mengting Zhao; Youhong Li; Lili Jin; Sumeng Xiang; Renzhi Pei; Ying Lu; Lei Jiang (Toxicology and Applied Pharmacology, 2024)

Pioneer plants promote soil formation in a mixture of bauxite tailings and red mud - Xusheng Jiang; Mengting Lin; Xuehong Zhang; Guo Yu; Pingping Jiang; Jie Liu (Journal of Environmental Management, 2024)

Effect of electron beam pretreated wheat flour on dough properties - Li Niu; Mengting Yan; Wei Liang; Qian Lin; Qi Zhao; Ruijie Li; Xinyu Wang; Raushan Moldakhmetova; Wenhao Li (Journal of Cereal Science, 2024)

High-performance static formation of methane hydrate in fixed bed constructed by incorporating expanded graphite into polyimide foam - Xinran Sun; Daiming Liu; Zhibing Xuan; Yongtao Zhang; Guodong Zhang; Chen Chen; Mengting Sun; Yan Lin; Jie Zhong; Fei Wang (Chemical Engineering Journal, 2024)

Investigating the influence of E-beam irradiated sorghum flour on the structure, physicochemical properties, and processing suitability of sorghum/wheat mixed flour-dough-bread: A related mechanism - Qian Lin; Wei Liang; Mengting Yan; Wenqing Zhao; Wenhao Li (Innovative Food Science & Emerging Technologies, 2024)

Gelsenicine disrupted the intestinal barrier of Caenorhabditis elegans - Zekai Wu; Jian Zhang; Yajiao Wu; Mengting Chen; Hong Hu; Xinyue Gao; Chutao Li; Maodong Li; Youbo Zhang; Xiaohuang Lin; Qiaomei Yang; Li Chen; et al. (Chemico-Biological Interactions, 2024)

ESG rating and financial risk of mining industry companies - Changluan Fu; Chenyang Yu; Mengting Guo; Lin Zhang (Resources Policy, 2024)

Toxic vascular effects of polystyrene microplastic exposure - Jianlong Yan; Yanbin Pan; Junbo He; Xinli Pang; Wenming Shao; Caiping Wang; Rongning Wang; Yaqiong He; Min Zhang; Juheng Ye; Chaolan Lin; Feng Lin; et al. (Science of The Total Environment, 2023)

Assessing forecasting performance of daily reference evapotranspiration: A comparative analysis of updated temperature penman-monteith and penman-monteith forecast models - En Lin; Rangjian Qiu; Mengting Chen; Hua Xie; Bushra Khurshid; Xinjuan Ma; Suolang Quzhen; Shizong Zheng; Yuanlai Cui; Yufeng Luo (Journal of Hydrology, 2023)

Complete genome sequence of a novel mitovirus detected in Colocasia esculenta - Mengting Wu; Chanchan Huang; Lin Wang; Bin Ke; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2023)

Using silkworm excrement to restore vegetation and soil ecology in heavily contaminated mining soils by multiple metal(loid)s: A recyclable sericulture measure - ShengJie Shi; JiGang Yang; MengTing Lin; QiaoYuan Chen; Bo Wang; JiaYi Zhao; Christopher Rensing; Hong Liu; ZhiLian Fan; RenWei Feng (Journal of Hazardous Materials, 2023)

Dendrobium officinale aqueous extract regulates bile acid synthesis to improve acute alcoholic liver injury in mice - Ju Ye; Di Wu; Xingdong Wu; Lin Qin; Mengting Yang; Yan-liu Lu; Dao-peng Tan; Yu-qi He (Food Bioscience, 2023)

Performance and mechanism of antibiotic removal by MOF-on-MOF-derived cobalt and nitrogen-doped magnetic porous carbon activated PMS - Kai Wang; Ping Xiang; Rongsheng Zhou; Mengting Huang; Pangshu Lin (Journal of Water Process Engineering, 2023)

Multi-trait analysis reveals large interspecific differences for phytoplankton in response to thermal change - Mengcheng Ye; Mengting Xiao; Shufei Zhang; Jiali Huang; Jiamin Lin; Yucong Lu; Shiman Liang; Jingyuan Zhao; Xiaoying Dai; Leyao Xu; Mingke Li; Yunyue Zhou; et al. (Marine Environmental Research, 2023)

Machine learning exploration of the mobility and environmental assessment of toxic elements in mining-associated solid wastes - Chongchong Qi; Mengting Wu; Hui Liu; Yanjie Liang; Xueming Liu; Zhang Lin (Journal of Cleaner Production, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Complete nucleotide sequence of hackberry virus A, a tentative member of the genus Waikavirus - Jiajia Weng; Mengting Wu; Zhuangxin Ye; Lin Wang; Bin Ke; Chanchan Huang; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; et al. (Archives of Virology, 2023)

Phenological responses of Bactrocera dorsalis (Hendel) to climate warming in China based on long-term historical data - Pumo Cai; Yunzhe Song; Litao Meng; Jia Lin; Mengting Zhao; Qingfeng Wu; Chuanpeng Nie; Yanyan Li; Qinge Ji (International Journal of Tropical Insect Science, 2023)
It is well accepted that the phenology of insects whose life activities are closely related to temperature is changing in response to global climate warming. To investigate the impacts of climate warming on the phenology of Bactrocera dorsalis (Hendel) across large temporal and spatial scales, this study collected historical data on the occurrence and population dynamic of this pest in China, and systematically explored its phenological responses. The results showed a delayed trend for the dates of first occurrence, end occurrence, population initial growth, and population peak of B. dorsalis in China during 40 years, and the changes of the latter two phenological parameters were significant. The mean temperature in spring and summer were the key climatic factors affecting the occurrence and population growth of B. dorsalis in China, respectively. Moreover, the B. dorsalis data in eastern, southern, central, and southwestern China showed spatial heterogeneity of phenological responses to climate warming at a regional scale. B. dorsalis phenology and their changing patterns with climate warming varied by geographical location. This study provides valuable information for future monitoring, prediction, and prevention of the oriental fruit fly in the context of climate warming.

Long-term adaptation to elevated temperature but not CO2 alleviates the negative effects of ultraviolet-B radiation in a marine diatom - Peng Jin; Jiaofeng Wan; Xiaoying Dai; Yunyue Zhou; Jiali Huang; Jiamin Lin; Yucong Lu; Shiman Liang; Mengting Xiao; Jingyuan Zhao; Leyao Xu; Mingke Li; et al. (Marine Environmental Research, 2023)

Production regions discrimination of Huangguanyin oolong tea by using the content of chemical components and rare earth elements - Shuxian Shao; Mengting Xu; Xiansheng Liao; Qin Luo; Yanping Lin; Pengjie Wang; Deyin Fang; Yibiao Huang; Shan Jin; Naixing Ye (Food Research International, 2023)

Non-destructive determination of internal defects in chestnut (Castanea mollissima) during postharvest storage using X-ray computed tomography - Jiahua Wang; Zelin Lu; Xiaofeng Xiao; Mengting Xu; Yuqing Lin; Huang Dai; Xiaodan Liu; Fuwei Pi; Donghai Han (Postharvest Biology and Technology, 2023)

Corrigendum to “Novel diketopyrrolopyrrole NIR-II fluorophores and DDR inhibitors for in vivo Chemo-photodynamic therapy of Osteosarcoma” [Chem. Eng. J. 446 (2022) 136929] - Xiaoding Cheng; Chong Zhang; Kun Shen; Huifan Liu; Caihong Bai; Qihang Ding; Mengting Guan; Junzhu Wu; Zhiquan Tian; Deliang Chen; Lin Cai; Xuechuan Hong; et al. (Chemical Engineering Journal, 2023)

Nitrous Oxide from Abiotic Processes of Hydroxylamine and Nitrite in Estuarine and Coastal Ecosystems: A Review - Chaobin Xu; Mengting Qi; Weisheng Lin; Xiaofei Li (Journal of Marine Science and Engineering, 2022)
Abiotic processes of nitrogen (N) are suggested to contribute to nitrous oxide (N2O) production; however, the important role of these processes in N2O emissions is invariably ignored. This review synthesized the main abiotic processes of hydroxylamine and nitrite and associated biogeochemical controls in estuarine and coastal ecosystems. Abiotic processes of hydroxylamine and nitrite are availably detected in estuarine and coastal environments. The abiotic processes of hydroxylamine contribute more to N2O production than the abiotic processes of nitrite in estuarine and coastal environments, suggesting that hydroxylamine plays an important role in N2O production. The isotopic fractionation effects of N can occur during the abiotic processes of hydroxylamine and nitrite and are enriched with the increasing rates of N reactions. In addition, abiotic processes of hydroxylamine and nitrite are highly dependent on pH, oxygen, Fe2+, Fe3+, and Mn4+ and are also triggered by the increasing substrate contents. These results suggest that abiotic processes of hydroxylamine and nitrite have been greatly concerned for the estuarine and coastal environments, whereas the dynamics of these processes are still sparse for projecting N fates and dynamics in response to environmental factors changes. This review highlights the importance of abiotic processes of N and associated environmental implications and presents the future trend of N cycling in estuarine and coastal environments.

sgRNACNN: identifying sgRNA on-target activity in four crops using ensembles of convolutional neural networks - Mengting Niu; Yuan Lin; Quan Zou (Plant Molecular Biology, 2021)

Identification and Expression Analysis of TCP Genes in Saccharum spontaneum L - Jishan Lin; Mengting Zhu; Mingxing Cai; Wenping Zhang; Mahpara Fatima; Haifeng Jia; Feifei Li; Ray Ming (Tropical Plant Biology, 2019)

Successional change in species composition alters climate sensitivity of grassland productivity - Zheng Shi; Yang Lin; Kevin R. Wilcox; Lara Souza; Lifen Jiang; Jiang Jiang; Chang Gyo Jung; Xia Xu; Mengting Yuan; Xue Guo; Liyou Wu; Jizhong Zhou; et al. (Global Change Biology, 2018)
Succession theory predicts altered sensitivity of ecosystem functions to disturbance (i.e., climate change) due to the temporal shift in plant community composition. However, empirical evidence in global change experiments is lacking to support this prediction. Here, we present findings from an 8‐year long‐term global change experiment with warming and altered precipitation manipulation (double and halved amount). First, we observed a temporal shift in species composition over 8 years, resulting in a transition from an annual C 3 ‐dominant plant community to a perennial C 4 ‐dominant plant community. This successional transition was independent of any experimental treatments. During the successional transition, the response of aboveground net primary productivity ( ANPP ) to precipitation addition magnified from neutral to +45.3%, while the response to halved precipitation attenuated substantially from −17.6% to neutral. However, warming did not affect ANPP in either state. The findings further reveal that the time‐dependent climate sensitivity may be regulated by successional change in species composition, highlighting the importance of vegetation dynamics in regulating the response of ecosystem productivity to precipitation change.

Effect of Temperature and pH on the Sorption of Dibutyl Phthalate on Humic Acid - Minling Gao; Xiaolei Gong; Mengting Lv; Wenhua Song; Xiaojun Ma; Yun Qi; Lin Wang (Water, Air, & Soil Pollution, 2016)

Responses of the functional structure of soil microbial community to livestock grazing in the T ibetan alpine grassland - Yunfeng Yang; Linwei Wu; Qiaoyan Lin; Mengting Yuan; Depeng Xu; Hao Yu; Yigang Hu; Jichuang Duan; Xiangzhen Li; Zhili He; Kai Xue; Joy van Nostrand; et al. (Global Change Biology, 2013)
Microbes play key roles in various biogeochemical processes, including carbon (C) and nitrogen (N) cycling. However, changes of microbial community at the functional gene level by livestock grazing, which is a global land‐use activity, remain unclear. Here we use a functional gene array, GeoChip 4.0, to examine the effects of free livestock grazing on the microbial community at an experimental site of T ibet, a region known to be very sensitive to anthropogenic perturbation and global warming. Our results showed that grazing changed microbial community functional structure, in addition to aboveground vegetation and soil geochemical properties. Further statistical tests showed that microbial community functional structures were closely correlated with environmental variables, and variations in microbial community functional structures were mainly controlled by aboveground vegetation, soil C/N ratio, and NH 4 + ‐N . In‐depth examination of N cycling genes showed that abundances of N mineralization and nitrification genes were increased at grazed sites, but denitrification and N‐reduction genes were decreased, suggesting that functional potentials of relevant bioprocesses were changed. Meanwhile, abundances of genes involved in methane cycling, C fixation, and degradation were decreased, which might be caused by vegetation removal and hence decrease in litter accumulation at grazed sites. In contrast, abundances of virulence, stress, and antibiotics resistance genes were increased because of the presence of livestock. In conclusion, these results indicated that soil microbial community functional structure was very sensitive to the impact of livestock grazing and revealed microbial functional potentials in regulating soil N and C cycling, supporting the necessity to include microbial components in evaluating the consequence of land‐use and/or climate changes.